Leadership in Action: A Question of Leadership: What Does Effective Leadership Look Like in a Virtual Work Environment? - Erskine, Laura (Center for Creative Leadership, 2009)
As organizations deal with advances in information and communication technologies, efforts to accommodate work-life balance and flex scheduling, and attempts to comply with the Americans with Disabilities Act, they are using virtual work to break down boundaries and connect employees-regardless of geographical location or subunit affiliation.